Synergistic Effects of Danshen (Salvia Miltiorrhiza Radix et Rhizoma) and Sanqi (Notoginseng Radix et Rhizoma) Combination in Inhibiting Inflammation Mediators in RAW264.7 Cells. (18th October 2016) - Zhou, Xian; Razmovski-Naumovski, Valentina; Chang, Dennis; Li, Chunguang; Kam, Antony; Low, Mitchell; Bensoussan, Alan; Chan, Kelvin
Abstract : Aims . This study aims to investigate the possible synergistic interactions of the Danshen-Sanqi combination on vascular disease via their anti-inflammatory activities. Methods . Nine combination ratios of Danshen-Sanqi extracts were screened in the RAW264.7 cell line and their anti-inflammatory effects were examined in lipopolysaccharide- (LPS-) induced nitric oxide (NO), tumor necrosis factor (TNF), and monocyte chemoattractant protein-1 (MCP-1) generation pathways. The interaction between Danshen and Sanqi on each target was analysed using combination index (CI) and isobologram models. Additionally, the anti-inflammatory activities of key bioactive compounds from Danshen and Sanqi were tested using the same models. The compounds from each herb that exerted the most potent activity were combined to evaluate their possible synergistic/antagonistic interactions. Results . Danshen-Sanqi 8 : 2 was found to be the optimal ratio and exerted a synergistic effect in inhibiting NO, TNF, and MCP-1 when the concentrations were higher than 1.24, 1.89, and 2.17 mg/mL, respectively. Although dihydrotanshinone I (DT) and ginsenoside Rd (Rd) from Danshen and Sanqi, respectively, exhibited the greatest individual bioactivity in the assays, antagonistic effects were observed for the DT-Rd combination 7 : 3. Conclusion . This study provided scientific evidence to support the traditional use of the Danshen-Sanqi combination for vascular disease through their synergistic interactions on anti-inflammatory pathways.